Safety and efficacy of cyclosporine (0.05% versus 0.09%) in dry eye disease. Is it the strength of cyclosporin that really matters? - Rajpoot, Mukesh; Singh, Divya; Pandey, Kankambari; Bhargava, Rahul (Nepalese Journal of Ophthalmology, 2022)
Introduction: This is a multicenter, randomized, interventional, double masked study aimed to compare safety and efficacy of cyclosporine (0.05% versus 0.09%) in dry eye disease. Materials and methods: Random allocation of patients (n=450) was done in two groups by parallel assignment (1:1). Group1(n=225) received CAs 0.05% drops twice daily, and group 2 (n=225) received CAs 0.09% drops twice daily for 3 months. Primary outcomes were changes from baseline in Lissamine green staining score, Nelson grade on conjunctival impression cytology and tear film osmolarity. Secondary outcomes were changes in dry eye symptom score. Schirmer’s test scores, changes in corneal fluorescein staining and changes in tear film break up time. Results: Within the groups, there was a significant improvement (ANOVA, P